2016
DOI: 10.3389/fmicb.2016.00047
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production by Selected Intestinal Microorganisms and Lactic Acid Bacteria Growing under Different Nutritional Conditions

Abstract: To gain some specific insight into the roles microorganisms might play in non-alcoholic fatty liver disease (NAFLD), some intestinal and lactic acid bacteria and one yeast (Anaerostipes caccae, Bacteroides thetaiotaomicron, Bifidobacterium longum, Enterococcus fecalis, Escherichia coli, Lactobacillus acidophilus, Lactobacillus fermentum, Lactobacillus plantarum, Weissella confusa, Saccharomyces cerevisiae) were characterized by high performance liquid chromatography for production of ethanol when grown on diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 66 publications
(76 reference statements)
1
84
0
2
Order By: Relevance
“…Bacteria community analysis, based on 16S rRNA gene sequencing, has revealed stark differences between metabolically-normal individuals and those with NAFLD and NASH. Broad phyla level (noted shifts in Bacteroidetes, Firmicutes, and Proteobacteria) changes have been reported and some have attempted to implicate specific bacterial strains with disease, although these observations remain preliminary 16–18 . Interestingly, stool bacterial community profiles of children with NAFLD are unique compared with adults with NAFLD, but this inconsistency might be expected given observations from others 19 .…”
Section: Influence Of Gut Microbiota On Metabolic Disease and Nafldmentioning
confidence: 99%
“…Bacteria community analysis, based on 16S rRNA gene sequencing, has revealed stark differences between metabolically-normal individuals and those with NAFLD and NASH. Broad phyla level (noted shifts in Bacteroidetes, Firmicutes, and Proteobacteria) changes have been reported and some have attempted to implicate specific bacterial strains with disease, although these observations remain preliminary 16–18 . Interestingly, stool bacterial community profiles of children with NAFLD are unique compared with adults with NAFLD, but this inconsistency might be expected given observations from others 19 .…”
Section: Influence Of Gut Microbiota On Metabolic Disease and Nafldmentioning
confidence: 99%
“…A number of studies have demonstrated that children and adolescents with NAFLD have increased serum ethanol levels, although this finding is not consistent across all studies . The gut microbiome can generate ethanol from dietary precursors, and manipulation of the gut microbiome is known to alter endogenous ethanol production . A common finding in NAFL and NASH is enrichment in Escherichia and/or Lactobacillus genera , which have the capability to produce ethanol.…”
Section: Gut Microbial Metabolism In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…(69) The gut microbiome can generate ethanol from dietary precursors, and manipulation of the gut microbiome is known to alter endogenous ethanol production. (128) A common finding in NAFL and NASH is enrichment in Escherichia and/ or Lactobacillus genera, (65,(68)(69)(70)(71)74,75,(77)(78)(79) which have the capability to produce ethanol. These findings suggest that increased endogenous ethanol production by the gut microbiome could contribute to the pathogenesis of NAFLD.…”
Section: Endogenous Ethanol Productionmentioning
confidence: 99%
“…fermentum produces lactate, acetate, and mannitol from the mixture of glucose and fructose in sugarcane juice. The acidic products cause a decrease in sugar consumption, growth inhibition of S. cerevisiae, and a decrease in ethanol production [64]. If S. cerevisiae is contaminated by L. fermentum, flocculation (co-aggregation) of S. cerevisiae with L. fermentum can occur [65][66][67].…”
Section: Fuel Ethanol Fermentationmentioning
confidence: 99%